Comparative analysis of skull morphology in the Sumatran rhinoceros of Borneo (Dicerorhinus sumatrensis harrissoni) - Danang Dwi Cahyadi; Deanty Chairunnisa; Supratikno; Savitri Novelina; Chairun Nisa'; Srihadi Agungpriyono; Dedi Chandra; Kurnia Oktavia Khairani; Zulfiqri; Muhammad Agil; Jono Adiputro; Matheas Ari Wibawanto; et al. (Zoologischer Anzeiger, 2026)

The art of bringing extinction to a freeze - History and future of species conservation - Thomas Hildebrandt; Susanne Holtze; Muhammad Agil; Pierfrancesco Biasetti; Julia Bohner; Miguel Casares; Loles Carbonell; Silvia Colleoni; Hayden Cuthill; Barbara De Mori; Sebastian Diecke; Cesare Galli; et al. (Cryobiology, 2025)

Sperm acrosome-associated 1 (SPACA1) mRNA and protein molecules deficiency indicate low fertility and semen quality of Bali bulls (Bos sondaicus) - Muhammad Agil; Berlin Pandapotan Pardede; Bambang Purwantara; Raden Iis Arifiantini; Hasbi Hasbi; Herry Sonjaya; Syahruddin Said; Suyadi Suyadi; Wike Andre Septian; Chairdin Dwi Nugraha; Rafika Febriani Putri; Ari Ardianto; et al. (Theriogenology, 2025)

Bovine nucleoprotein transitions genes and protein abundance as valuable markers of sperm motility and the correlation with fertility - Berlin Pandapotan Pardede; Ni Wayan Kurniani Karja; Syahruddin Said; Ekayanti Mulyawati Kaiin; Muhammad Agil; Cece Sumantri; Bambang Purwantara; Iman Supriatna (Theriogenology, 2024)

Factors Affecting the Outcome and Intensity of Intergroup Encounters in Crested Macaques (Macaca nigra) - Laura Martínez-Íñigo; Rismayanti; Antje Engelhardt; Muhammad Agil; Malgorzata Pilot; Bonaventura Majolo (International Journal of Primatology, 2023)
Conspecific animal groups often compete for access to fitness-enhancing resources. The more valuable the resource at stake is, the greater the costs groups can afford to outcompete their neighbours, leading to between-group conflicts. We investigated what factors affected intergroup encounter outcome (win, loss, or draw) and intensity (level of aggression and duration) in wild, crested macaques ( Macaca nigra ). We collected data on 158 dyadic intergroup encounters among three groups of crested macaques in Tangoko Nature Reserve (Indonesia) between November 2015 and July 2016. Intergroup encounters were more likely to have a clear winner the larger the group size difference was between the opposing groups and when both groups rarely used the intergroup encounter location. Groups tended to win in specific parts of their home range, regardless of the numerical advantage, the frequency of use of the intergroup encounter location and its distance to the closest core area. Most encounters involved aggression, but contact aggression was rare. None of our candidate predictors helped to explain the differences in intergroup encounter escalation. Male intergroup aggression was more common than female intergroup aggression. The probability of female and male participation in intergroup aggression increased with the participation of the other sex. Males chased and attacked females in their group (i.e., herded them) in most encounters. Our study suggests that intragroup sexual conflict occurs during intergroup encounters in crested macaques. More detailed and longer studies on intergroup participation may help to understand the factors behind crested macaque intergroup encounter outcome and intensity.

Climate, Temporal Abundance of Key Food Sources and Home Ranges of Crested Macaques (Macaca nigra) in Sulawesi, Indonesia: A Longitudinal Phenological Study - Marine Joly; Meldy Tamengge; Jan-Boje Pfeiffer; Megan Price; Muhammad Agil; Antje Engelhardt (International Journal of Primatology, 2023)
Climate change is associated with more frequent extreme weather conditions and an overall increase in temperature around the globe. Its impact on individual ecosystems is not yet well known. Long-term data documenting climate and the temporal abundance of food for primates are scarce. We used long-term phenological data to assess climate variation, fruit abundance and home range sizes of the endemic and Critically Endangered crested macaques ( Macaca nigra ) in Tangkoko forest, Sulawesi, Indonesia. Between January 2012 and July 2020, every month, we monitored 498 individual trees from 41 species and 23 families. We noted each tree’s phenophase and assessed variation in climate (daily temperature and rainfall) and fruit abundance. We also investigated whether individual trees of known key food sources for macaques (New Guinea walnut trees, Dracontomelon spp , two species, N = 10 individual trees; fig trees, Ficus spp , four species, N = 34, and spiked peppers, Piper aduncum , N = 4) showed regular and synchronised fruiting cycles. We used 2877 days of ranging data from four habituated groups to estimate home ranges between January 2012 and July 2020. We created models to evaluate the impact of ecological factors (temperature, rainfall, overall fruit abundance, fig abundance). We found that the temperature increased in Tangkoko forest, and the overall fruit abundance decreased across the study. Top key fruits showed different trends in fruiting. Figs seem to be present year-round, but we did not detect synchrony between individuals of the same species. The macaque home ranges were about 2 km 2 . Monthly temperature was the main predictor of home range size, especially in disturbed forest with previously burnt areas. This information will help to further monitor changes in the macaques’ habitat, and better understand ranging and foraging strategies of a Critically Endangered species and hence contribute to its conservation.

Ten Years of Positive Impact of a Conservation Education Program on Children's Knowledge and Behaviour Toward Crested Macaques (Macaca nigra) in the Greater Tangkoko Area, North Sulawesi, Indonesia - Mathilde Chanvin; François Lamarque; Nona Diko; Muhammad Agil; Jérôme Micheletta; Anja Widdig (International Journal of Primatology, 2023)
In areas where primates are threatened, environmental education interventions are a key way to increase the local population’s knowledge of their environment and encourage positive attitudes and habits to preserve the environment and wildlife on a local and global scale. This study assesses the impact of Tangkoko Conservation Education (TCE), the Macaca Nigra Project’s conservation education programme, running since 2011 in North Sulawesi for school children, teachers, and the local population. TCE’s goal is to help people increase their knowledge of their environment and develop more positive habits and behaviours towards their local environment, especially the Critically Endangered and endemic crested macaques ( Macaca nigra ). We measured the efficacy of TCE’s programme for pupils using questionnaires provided one month before and one month after a year-long conservation education programme at school. Pupils’ knowledge and behaviour scores increased significantly after their participation in the programme. Their habits score also increased but this increase was not statistically significant. Girls scored significantly higher than boys in terms of positive behaviour towards wildlife. Children participating in the programme more than once seemed to obtain higher scores in their second participation, although the sample size was too small for formal analysis. Despite some limitations, this study demonstrates the positive impact of our programme on young people living in an area where primates are threatened. We hope that this research will inspire similar programmes in Sulawesi and elsewhere by providing methods and activities to help prevent primate extinction.

The cost of associating with males for Bornean and Sumatran female orangutans: a hidden form of sexual conflict? - Julia A. Kunz; Guilhem J. Duvot; Maria A. van Noordwijk; Erik P. Willems; Manuela Townsend; Neneng Mardianah; Sri Suci Utami Atmoko; Erin R. Vogel; Taufiq Purna Nugraha; Michael Heistermann; Muhammad Agil; Tony Weingrill; et al. (Behavioral Ecology and Sociobiology, 2021)
Sexual coercion, in the form of forced copulations, is relatively frequently observed in orangutans and generally attributed to their semi-solitary lifestyle. High ecological costs of association for females may be responsible for this lifestyle and may have prevented the evolution of morphological fertility indicators (e.g., sexual swellings), which would attract (male) associates. Therefore, sexual conflict may arise not only about mating per se but also about associations, because males may benefit from associations with females to monitor their reproductive state and attempt to monopolize their sexual activities. Here, we evaluate association patterns and costs for females when associating with both males and females of two different orangutan species at two study sites: Suaq, Sumatra ( Pongo abelii ), and Tuanan, Borneo ( Pongo pygmaeus wurmbii ). Female association frequency with both males and females was higher in the Sumatran population, living in more productive habitat. Accordingly, we found that the cost of association, in terms of reduced feeding to moving ratio and increased time being active, is higher in the less sociable Bornean population. Males generally initiated and maintained such costly associations with females, and prolonged associations with males led to increased female fecal cortisol metabolite (FCM) levels at Tuanan, the Bornean population. We conclude that male-maintained associations are an expression of sexual conflict in orangutans, at least at Tuanan. For females, this cost of association may be responsible for the lack of sexual signaling, while needing to confuse paternity. Significance statement Socioecological theory predicts a trade-off between the benefits of sociality and the ecological costs of increased feeding competition. Orangutans’ semi-solitary lifestyle has been attributed to the combination of high association costs and low predation risk. Previous work revealed a positive correlation between association frequencies and habitat productivity, but did not measure the costs of association. In this comparative study, we show that females likely incur costs from involuntary, male-maintained associations, especially when they last for several days and particularly in the population characterized by lower association frequencies. Association maintenance therefore qualifies as another expression of sexual conflict in orangutans, and especially prolonged, male-maintained associations may qualify as an indirect form of sexual coercion.

Comparison of fecal preservation and extraction methods for steroid hormone metabolite analysis in wild crested macaques - Gholib Gholib; Michael Heistermann; Muhammad Agil; Iman Supriatna; Bambang Purwantara; Taufiq Purna Nugraha; Antje Engelhardt (Primates, 2018)

Validation of a field-friendly extraction and storage method to monitor fecal steroid metabolites in wild orangutans - Taufiq Purna Nugraha; Michael Heistermann; Muhammad Agil; Bambang Purwantara; Iman Supriatna; Gholib Gholib; Carel P. van Schaik; Tony Weingrill (Primates, 2017)

Mother-male bond, but not paternity, influences male-infant affiliation in wild crested macaques - Daphne Kerhoas; Lars Kulik; Dyah Perwitasari-Farajallah; Muhammad Agil; Antje Engelhardt; Anja Widdig (Behavioral Ecology and Sociobiology, 2016)

Costs of and Investment in Mate-Guarding in Wild Long-Tailed Macaques (Macaca fascicularis): Influences of Female Characteristics and Male–Female Social Bonds - Cédric Girard-Buttoz; Michael Heistermann; Erdiansyah Rahmi; Muhammad Agil; Panji Ahmad Fauzan; Antje Engelhardt (International Journal of Primatology, 2014)

Mate-guarding constrains feeding activity but not energetic status of wild male long-tailed macaques (Macaca fascicularis) - Cédric Girard-Buttoz; Michael Heistermann; Erdiansyah Rahmi; Anna Marzec; Muhammad Agil; Panji Ahmad Fauzan; Antje Engelhardt (Behavioral Ecology and Sociobiology, 2014)